2019
DOI: 10.1002/mbo3.816
|View full text |Cite
|
Sign up to set email alerts
|

ESBL‐production in Escherichia coli and Klebsiella pneumoniae isolates from Nigeria

Abstract: The worldwide increase in infections caused by extended‐spectrum beta‐lactamase‐ (ESBL) and AmpC‐producing Enterobacteriaceae (ESBL‐E) is a concern. Surveillance is extensive in Europe, North America, and Asia. Yet, there is no summarizing surveillance in Africa. This study aimed to perform a preliminary investigation on the prevalence of ESBL‐E in the northeastern part of Nigeria. However, of the 60 samples collected, we were able to culture 15 Escherichia coli and 7 Klebsiella spp. only. In the collection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 3 publications
3
4
1
Order By: Relevance
“…Several studies have reported that AmpC producer in K. pneumoniae ranged from 7.8% to 43%. [37][38][39] Similar to a previous study, resistance to carbapenem among Enterobacter spp. was high.…”
Section: Discussionsupporting
confidence: 81%
“…Several studies have reported that AmpC producer in K. pneumoniae ranged from 7.8% to 43%. [37][38][39] Similar to a previous study, resistance to carbapenem among Enterobacter spp. was high.…”
Section: Discussionsupporting
confidence: 81%
“…In our study, the detection rates of ESBL in E. coli- EOD and E. coli- LOD groups were 25.76 and 32.14%, respectively. These figures were significantly lower than those reported in other regions of China (45.4%) and in studies conducted overseas (53%) [ 29 , 30 ]. This is likely attributable to less frequent use of cephalosporins in the neonatal department of our hospital, more intensive monitoring of bacterial resistance, and to the regional differences.…”
Section: Discussioncontrasting
confidence: 73%
“…The widespread use of broad-spectrum antibiotics, especially the abuse of third-generation cephalosporins, is the main reason for the increase of ESBL producing strains. The mechanism of drug resistance of ESBL-positive E. coli strains is drug-induced target gene mutation; in addition, plasmid-mediated transmission among different strains leads to wide spread of drug-resistant strains [ 29 ]. In our study, the detection rates of ESBL in E. coli- EOD and E. coli- LOD groups were 25.76 and 32.14%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that 48.78% of analyzed Enterobacteriaceae presented the characteristic ESBL-production phenotype, being E. coli and K. pneumoniae the most common species which presented this phenotype; similar results have been reported in different countries [26,27]. Although K. pneumoniae has stood out as one of the most common producers of ESBLs, it should be noted that in recent years, ESBLproducing E. coli has gained importance worldwide [28,29].…”
Section: Esbl-producing Enterobacteriaceae Distributionsupporting
confidence: 87%